1989
DOI: 10.1084/jem.169.4.1467
|View full text |Cite
|
Sign up to set email alerts
|

An L-arginine-dependent mechanism mediates kupffer cell inhibition of hepatocyte protein synthesis in vitro

Abstract: The hepatic failure associated with severe sepsis is characterized by specific, progressive, and often irreversible defects in hepatocellular metabolism (1). Although the etiologic microbe can often be identified, the direct causes and mechanisms of the hepatocellular dysfunction are poorly understood . We have hypothesized that Kupffer cells (KC), which interact with ambient septic stimuli, respond by providing signals to adjacent hepatocytes (HC) in sepsis . Furthermore, we have provided evidence (2, 3) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
104
0
4

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(109 citation statements)
references
References 13 publications
(23 reference statements)
1
104
0
4
Order By: Relevance
“…27 Several studies have shown that both Kupffer cells and hepatocytes themselves synthesize NO. 28,29 In LPS treated rats portal and systemic plasma nitrite and nitrate levels (considered markers of NO production) are increased over 40-fold compared with normal rats as a result of iNOS induction by LPS. 30 Chronic exposure to sublethal levels of endotoxin, as occurs FIG.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies have shown that both Kupffer cells and hepatocytes themselves synthesize NO. 28,29 In LPS treated rats portal and systemic plasma nitrite and nitrate levels (considered markers of NO production) are increased over 40-fold compared with normal rats as a result of iNOS induction by LPS. 30 Chronic exposure to sublethal levels of endotoxin, as occurs FIG.…”
Section: Discussionmentioning
confidence: 99%
“…24 This possibility has been supported by the recognition of GD' s potent ability to block calcium channels in muscle cells, 26 endothelial cells, 27 and neuroendocrine cells. 28 The ability of the chelating agents, ethylene glycol-bis(␤-aminoethyl-ether)-N,N-tetraacetic acid, 29 and the orthophosphate salts, NaH 2 PO 4 and KH 2 PO 4 , 30 to reverse the GD blockage suggest that GD ions act extracellularly, probably near the mouth of the Ca ϩϩ channel. The failure of lathanide to affect the 340-nm and 380-nm excitation of fura-2-loaded cells also strongly suggested an extracellular effect.…”
mentioning
confidence: 99%
“…1,7 Secondly, KC release tumor necrosis factor ␣ (TNF-␣) and prostaglandin E 2 (PGE 2 ), among other factors, in response to in vitro stimulation with LPS. 3,4,8,9 In addition, elevated blood levels of TNF-␣ 10 and enhanced monocyte release of PGE 2 11-13 characterize the human septic response. The critical role of TNF-␣ in the experimental septic response has been supported by the prevention of septic mortality with anti-TNF-␣ antibodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 NO has been implicated in the regulation of a number of cell processes, 3 including the transport of Na ϩ across the cell membranes in proximal renal tubules, 4 and of HCO 3Ϫ and glutathione in the liver. 5 NO also plays an important role in iron homeostasis, mainly by modulating the activity of iron regulatory proteins (IRPs).…”
mentioning
confidence: 99%